Using biomass to increase the efficiency of heat pump installations. - D. V. Petrov; R. E. Berezhnoy; V. V. Sakunov (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. Increasing the efficiency of residential heating systems is one of the priority tasks of the thermal power industry. One way to increase the energy efficiency of heating is to use heat pumps (HP).Goal. Justification of a method for increasing the efficiency of heat pumps.Materials and methods. The research is based on empirical methods of direct and indirect observations, analytical and experimental methods.Results and discussion. The efficiency of a heat pump is determined by the thermal transformation coefficient, which is higher the higher the temperature of the low potential heat source (LPH). This work shows the possibility of effectively using the heat of organic waste (biomass) as an LPH, the fermentation temperature of which can reach quite high values. Conducted experiments and theoretical calculations show a significant increase in the efficiency of HP with increasing temperature of the LPH.Conclusion. When using biomass as LPH, the conversion coefficient of the heat pump reaches 5...7 units, which allows it to be used as an alternative to gas heating. The experiments carried out confirm the theoretical calculations of the conversion coefficient, and we can talk about the economic efficiency of using such heat pump units.